Penatalaksanaan Fisioterapi Pada Subluksasi Acromioclavicular Joint Dextra Di RSUD Sragen - MARASINTA, Ista Suhada (2015)
Background : An AC Joint Subluxation is a partial dislocation, meaning that the clavicle goes partially out of joint, with part of the clavicle still touching the acromion. An AC Joint Subluxation looks like a small bump on top of the shoulder. Physio management at the Acromionclavicular Subluxation with physiotherapy modalities, namely : Infra Red ( IR ), Short Wave Diathermy ( SWD ), and Therapeutic Exercise. Aim Of Research : To study about the management of physiotherapy in reducing pain, increasing range of motion, and improve muscle strength in patients with an acromioclavicular joint subluxation using Infra Red, Short Wave Diathermy (SWD), and Therapy Exercise. Results : After therapy for about six times the obtained results of the assessment of pain in motion pain T1 : 6 to T6 : 3, tenderness T1 : 4 to T6 : 2, painful silence T1 : 4 to T6 : 2. Increasing range of motion S : T1 : 20˚-0˚-130˚ to T6 : 45˚-0˚-165˚, F : T1 : 140˚-0˚-30˚ to T6 : 165˚-0˚-30˚, T : T1 : 10˚-0˚-110˚ to T6 : 30˚-0˚-130˚, R(F 90) : T1 : 50˚-0˚-30˚ to T6 : 70˚-0˚-75˚. And improve muscle strength flexion, ekstension, elevasion, protraksion, retraksion, abduksion HR, endorotasion, eksorotasion from T1 : 3- to T6 : 4, depresion and adduksion HR from T1 : 4- to T6 : 4+. Conclusion : Short Wave Diathermy (SWD) can reduce pain in the acromioclavicular joint subluxation dextra, Exercise Therapy (ET) can improve range of motion and muscle strength.